1995
DOI: 10.1074/jbc.270.51.30664
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of H2B-V Encoding a Particular H2B Histone Variant Causes Changes in Protein Patterns on Two-dimensional Polyacrylamide Gel Electrophoresis in the DT40 Chicken B Cell Line

Abstract: The chicken H2B gene family comprises eight members (H2B-I to H2B-VIII), which are all located in two major histone gene clusters. All of them have been shown to encode four different protein variants (classes I to IV). In the DT40 chicken B cell line, the H2B-V gene, encoding the class III H2B variant, constituted about 10% of the total intracellular mRNA from all the H2B genes. To study the nature of this particular variant in vivo, we generated heterozygous (H2B-V, ؉/؊) and homozygous (H2B-V, ؊/؊) DT40 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…DT40 cells and all subclones were cultured essentially as described (Buerstedde & Takeda 1991;Takeda et al 1992;Takami et al 1995aTakami et al , 1995b) in Dulbecco's modified medium containing 10% (v/v) foetal calf serum, 1% (v/v) chicken serum, 2 mM L-glutamine, 0.01 mM 2-mercaptoetanol, and penicillin and streptomycin at 37 ЊC under 5% CO 2 in air in a humidified incubator. At the indicated times, the cells were counted to determine the growth rate.…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…DT40 cells and all subclones were cultured essentially as described (Buerstedde & Takeda 1991;Takeda et al 1992;Takami et al 1995aTakami et al , 1995b) in Dulbecco's modified medium containing 10% (v/v) foetal calf serum, 1% (v/v) chicken serum, 2 mM L-glutamine, 0.01 mM 2-mercaptoetanol, and penicillin and streptomycin at 37 ЊC under 5% CO 2 in air in a humidified incubator. At the indicated times, the cells were counted to determine the growth rate.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Moreover, it has been reported that in Saccharomyces cerevisiae, the deletion of H4 N-terminal residues 4-23 or mutagenesis of the acetylatable lysines in this region decreases the activation of the GAL1 promoter, while the deletion of N-terminal residues 4-15 of H3 or the mutagenesis of the acetylatable lysines causes a hyperactivation of GAL1 (Fisher-Adams & Grunstein 1995). We recently established that the targeted disruption of H2B-V, encoding one of four H2B variants, causes changes in protein patterns in the DT40 chicken B cell line, indicating that the variant may participate in the regulation of expression of putative genes encoding the proteins that varied in the H2B-V deficient DT40 mutant (Takami et al 1995a). These results, together with other observations (van Daal & Elgin 1992), indicated that eukaryotic core histones affect the expression of specific genes both positively and negatively.…”
Section: Introductionmentioning
confidence: 99%
“…Transfection was carried out essentially as described (36,37). To obtain ⌬HIRA cells, transfectants with the p⌬HIRA/neo construct were first selected in medium containing 2 mg of neomycin (neo; G-418) per ml.…”
Section: Methodsmentioning
confidence: 99%
“…Gene Constructs, Transfection, and Isolation of Transfectants-Two blunt-ended cassettes, carrying neo and hisD, respectively (41), transcribed by the chicken ␤-actin promoter (42,43), were obtained as described (26,28). Using these cassettes, we generated targeting vectors for the disruption of chHDAC-1 and -2, as follows.…”
Section: Methodsmentioning
confidence: 99%
“…the growth rate and global chromatin structure, indicating that only one copy of the H1 genes is enough for cell proliferation (31). Third, the protein patterns are altered in the mutants, respectively, lacking particular H1 and H2B variants (26,28,30,31), and the variable proteins are specific for the corresponding mutants, suggesting that the H1 and core variants should be individually involved in regulation of the expression of specific genes. These results, together with those obtained for a number of different genes (33)(34)(35), suggest that the DT40 cell line should be most useful for an in vivo understanding of the roles of important genes in higher eukaryotes.…”
mentioning
confidence: 99%